KETERKAITAN ANTARA KOMITMEN AFEKTIF DENGAN INTENSI TURNOVER PADA KARYAWAN BAGIAN PRODUKSI DI PT. USMAN JAYA MEKAR MAGELANG - Rokhmah, Betty Eliya; Riani, Asri Laksmi (Universitas Muhammadiyah Surakarta, 2005)
This study analyzes the direct effect of affective commitment to the supervisor on turnover intention and the indirect effect of affective commitment to the supervisor and affective commitment to the work group on turnover intention with affective commitment to the organization being mediating variable. By using Structural Equation Modeling (SEM) which assisted by application program of Analysis of Moment Structure (AMOS), the result indicated that affective commitment to the supervisor and work group have indirect effect only on turnover intention. The indirect effect is mediated by affective commitment to the organization. The suggestions for further study and the limitation of this research are discussed.